ANALISIS PENGARUH JUMLAH PENDUDUK DAN USIA HARAPAN HIDUP TERHADAP JUMLAH PENDUDUK MISKIN DI SETIAP WILAYAH KABUPATEN/KOTA DI PROVINSI JAWA TENGAH TAHUN 2022 - Ardilla Avi Prasetya; Ridayati Ridayati (LPPM Universitas Ekasakti, 2024)
The purpose of this study is to determine the relationship between the population of Central Java Province, life expectancy, and the percentage of poor people. By using cross-section data from Dispermadesdukcapil and Central Java Provincial Statistics Agency, the technical used is multiple linear regression analysis. The results show that Life Expectancy has a significant negative effect on the number of poor people, while Population does not have a significant effect on the number of poor people. Thus, increasing Life Expectancy can be an effective strategy in reducing poverty in Central Java Province. These results have important implications in formulating more appropriate policies to reduce poverty in the region.